Das traditionelle chinesische Theater : vom Mongolendrama bis zur Pekinger Oper - Kubin, Wolfgang (Geschichte der chinesischen Literatur ;, 2009)
As early as the Mongol Age - at a time when dramatic art had not yet been rediscovered in Europe - Chinese theatre blossemed. Providing a historical overview, this volume analyses the emerge of the Chinese stage in religion as well as the reception of Chinese theatre in the western world.